2017
DOI: 10.1007/s00417-017-3652-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of fellow eye in patients with lamellar macular hole

Abstract: Our data suggest that the presence of a LMH in one eye does not increase significantly the risk of developing the same condition in the fellow eye after 4 years. Bilateral condition is uncommon, and an ERM is often detected in the fellow eye. LHEPs were not observed in fellow eyes with foveal integrity, and all LHEPs observed (in main and fellow eyes) were always associated with LMHs; this supports the hypothesis that LHEP is a consequence and not a causative factor for LMHs. The occurrence of a LMH in one fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Bilateral LMH appears to be a relatively uncommon occurrence [ 23 ]. A retrospective study of 35 individuals with a LMH revealed that in the fellow eye, 83% had a vitreomacular abnormality.…”
Section: Epidemiologymentioning
confidence: 99%
“…Bilateral LMH appears to be a relatively uncommon occurrence [ 23 ]. A retrospective study of 35 individuals with a LMH revealed that in the fellow eye, 83% had a vitreomacular abnormality.…”
Section: Epidemiologymentioning
confidence: 99%
“…According to the pathological hypothesis of LMH as an abortive process of FTMH, such a complication can occur. 13 , 14 It should be considered whether vitrectomy at an earlier stage can prevent FTMH development.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 8–12 One hypothesis is that it could occur after PVD as an abortive process of a full thickness macular hole (FTMH) formation. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…2325 A higher occurrence of bilateral macular disorders and pathological changes in the morphology of the vitreoretinal interface have also been noted in the fellow eyes over a longer time span. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] A higher occurrence of bilateral macular disorders and pathological changes in the morphology of the vitreoretinal interface have also been noted in the fellow eyes over a longer time span. 26,27 Interestingly, Kay and colleagues 28 reported increased familial occurrence of MHs in patients with idiopathic MH, as compared with controls. This trend was more common in patients with bilateral MH, a factor which was seen to persist even after disregarding confounding factors such as age and number of relatives suffering from the syndrome.…”
Section: Discussionmentioning
confidence: 99%